Festuca and allied genera (Poaceae) as Crop Wild Relatives: Checklists and Red Lists are urgently required. (2nd January 2017) - Ardenghi, N. M. G.; Foggi, B.; Orsenigo, S.; Maggioni, L.; Cauzzi, P.; Rossi, G.
Abstract: Festuca s.l. is a crucial group of Crop Wild Relatives (CWR) genera, globally employed as fodder, lawn grasses and for habitat restoration. Lists elaborated strictly on the basis of a taxonomic approach are urgently needed to be used to find gaps in existing ex situ collections, to assess the conservation status of taxa of ascertained utility and include them in national Red Lists and to identify the most valuable taxa to be included in "preservation mixtures", as per Commission Directive 2010/60/EU. As an example, the first taxonomically based priority list of Italian CWRs of Festuca s.l. is here provided.